Legal and Research Considerations regarding the Importance of Developing and Nurturing Trusting Family-Professional Partnerships in Special Education Consultation. Issue 4 (1st October 2020) - Gershwin, Tracy
ABSTRACT: Over the past 30 years, through multiple reauthorizations, both the Every Student Succeeds Act, and the Individuals with Disabilities Education Act, lawmakers and researchers have consistently acknowledged the importance of fostering family-professional partnerships in schools. Yet research continues to document a number of challenges and obstacles experienced by families and professionals with actualizing this intended partnership through both special meetings (i.e., Individualized Education Programs) and ongoing consultation interactions, as originally envisioned by lawmakers. Much of this divergence between policy, research, and practice is attributed to the historical challenges experienced between professionals and families with forming and maintaining trust. In celebration of the Journal of Educational and Psychological Consultation's 30 th anniversary, this paper provides discussion of the legal implications of the family-professional partnership, historical documented challenges that lead to a lack of trust in these partnerships, the importance of developing and maintaining a trusting family-professional partnership in special education consultation, and recommendations for future family/parent consultation practice, research, and policy.